"UNFRIEND ME, PLEASE!": SOCIAL MEDIA FATIGUE AND THE THEORY OF RATIONAL CHOICE. Issue 4 (2nd October 2018) - Logan, Kelty; Bright, Laura F.; Grau, Stacy Landreth
Abstract : As social media use continues to climb, consumers are beginning to experience social media fatigue leading to concern among marketers about the efficacy of the channel. This research examines social media fatigue through the lens of the Theory of Rational Choice to better understand how consumers cope with this phenomenon and how it impacts brands. Our findings suggest that growing privacy concerns lead to social media fatigue among U.S. consumers. However, consumers' conscious decision to remain involved in social media reflects their belief that continued use provides outcomes that are more positive than discontinuance of use.